(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
COVID-19 infection is ubiquitous now, and it is not unusual to find various clinical presentations of this notorious infection; nevertheless, the common infection site is the respiratory epithelium or lung parenchyma; hence, SARS-CoV-2 is most commonly isolated from the respiratory tract by a real-time polymerase chain reaction (RT-PCR) assay, and is considered as a gold-standard test for COVID-19 diagnosis. We reported a case presented with a right-side pleural effusion and underlying consolidation, and aspirated transudative pleural fluid revealed a positive COVID-19 RT-PCR result. So far, only a few positive pleural fluid COVID-19 RT-PCR cases have been reported; however, our case was detected in mid-2020.